Syntheses and biological properties of brefeldin analogues - Förster, Sebastian; Persch, Elke; Tverskoy, Olena; Rominger, Frank; Helmchen, Günter; Klein, Christian D.; Özata, Başak; Brügger, Britta (European journal of organic chemistry, 2011)
Total and partial syntheses of brefeldin analogues are described. (6R)-Hydroxy-BFA (5) was obtained through a total synthesis from (1S,2R)-2-[(trityloxy)methyl]cyclopent-3-ene-1-carbonitrile (cis-8) in 13 steps. The BFA lactam analogue 6 was prepared via the key building block 25, which was accessed in four steps from BFA (1). (7S)-Amino-BFC (7) was obtained from 7-dehydro-BFA (3) by reductive amination. The structures of the brefeldin analogues were determined by X-ray analyses. The activities of the brefeldin analogues in blocking protein traffic between the endoplasmatic reticulum and the Golgi apparatus were determined both for mammalian cells and for plant cells. Molecular mechanics calculations and docking into the Arf1-GEF protein complex, an established receptor of BFA, were carried out.
Online veröffentlicht: Dezember 30, 2010
Gesehen am 09.02.2023